2022
DOI: 10.1007/s10886-022-01383-1
|View full text |Cite
|
Sign up to set email alerts
|

Links Between Feeding Preferences and Electroantennogram Response Profiles in Dung Beetles: The Importance of Dung Odor Bouquets

Abstract: The detection of dung odors is a crucial step in the food-searching behavior of dung beetles (Coleoptera: Scarabaeoidea). Yet, whether certain compounds characteristic of a given dung type contribute to a ‘choosy generalism’ behavior proposed for this taxonomic group is unknown. To address this, we analyzed the chemical composition of three types of dung (cow, horse, and rabbit) and conducted behavioral and electroantennogram (EAG) bioassays on 15 species of dung beetles using 19 volatile organic compounds rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…Considering the important chemosensory interaction that dung beetles have with an ephemeral resource like dung via their olfactory system (Cortez et al, 2016;Inouchi et al, 1988;Riffell, 2012), the absence of a significant difference in T A B L E 2 Chemical profiles of dung volatile emissions of different dung types analysed by gas chromatography-mass spectrometry. the chemical profile of the volatile compounds emitted by the treatments with IVM would explain the similar behavioural responses exhibited by the model species (Urrutia et al, 2022). In at least half of the studies analysed in Table 1, no concrete difference in attraction was verified between cattle dung from treated and non-treated animals, despite the diverse methods of IVM application and methodologies employed in their observations.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Considering the important chemosensory interaction that dung beetles have with an ephemeral resource like dung via their olfactory system (Cortez et al, 2016;Inouchi et al, 1988;Riffell, 2012), the absence of a significant difference in T A B L E 2 Chemical profiles of dung volatile emissions of different dung types analysed by gas chromatography-mass spectrometry. the chemical profile of the volatile compounds emitted by the treatments with IVM would explain the similar behavioural responses exhibited by the model species (Urrutia et al, 2022). In at least half of the studies analysed in Table 1, no concrete difference in attraction was verified between cattle dung from treated and non-treated animals, despite the diverse methods of IVM application and methodologies employed in their observations.…”
Section: Discussionmentioning
confidence: 94%
“…The olfactometer bioassays demonstrated that no significant differences in the attraction of the dung beetle A. cicatricosus to the different dung samples from untreated cattle (control), treated cattle and IVM‐spiked occur. Considering the important chemosensory interaction that dung beetles have with an ephemeral resource like dung via their olfactory system (Cortez et al, 2016; Inouchi et al, 1988; Riffell, 2012), the absence of a significant difference in the chemical profile of the volatile compounds emitted by the treatments with IVM would explain the similar behavioural responses exhibited by the model species (Urrutia et al, 2022). In at least half of the studies analysed in Table 1, no concrete difference in attraction was verified between cattle dung from treated and non‐treated animals, despite the diverse methods of IVM application and methodologies employed in their observations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations